Syllabic pseudohomophone priming in tip-of-the-tongue states resolution: The role of syllabic position and number of syllables. Issue 5 (May 2013) - Pureza, Rita; Soares, Ana Paula; Comesaña, Montserrat
The tip-of-the-tongue (TOT) state is a common experience, usually coupled with a frustrating feeling caused by the incapability of retrieving a familiar word. It is thought that TOTs occur when the semantic and syntactic information of the word is retrieved but not its phonology. This study aims to further understand the role of phonology in TOT resolution. Specifically, using a syllabic pseudohomophone priming paradigm, we aim to analyse the role of the phonological syllabic position (first vs. last) and the number of syllables in TOT states resolution. TOT was elicited by a picture naming task, after which a lexical decision task was presented. Here, first, last, or none of the phonological syllables of the target word were embedded in pseudohomophone primes. Results showed a significant syllabic pseudohomophone priming effect facilitating TOT resolution. The effect was stronger for four-syllable words, especially when the last syllable was used as prime. These results seem to reinforce the importance of phonology in TOT states resolution, particularly the role of the syllable as an important sublexical unit in speech processing.